Vase life extension of cut hydrangea (Hydrangea macrophylla) flowers. Issue 3 (3rd May 2020) - Kazaz, Soner; Kılıç, Tuğba; Doğan, Ezgi; Sekmen, Şafak
ABSTRACT: The popularity of cut hydrangea has been increasing in the global floriculture market in recent years. However, vase life of cut hydrangeas is shortened due to sepal browning and wilting. This study was conducted to find out a vase life solution in extending the vase life of cut hydrangea ( Hydrangea macrophylla cv. Schneeball) flowers. Cut hydrangea stems were placed in solutions containing 8-hydroxyquinoline sulphate (100, 200 and 300 mgL −1 ), glycolic acid (9.5, 19 and 28 mgL −1 ) and distilled water which was used as the control. The vase life, relative fresh weight and solution uptake were measured. Compared to the control, the vase life of cut hydrangeas were significantly increased by all 8-HQS treatments. The best concentration of 8-HQS was 200 mgL −1 and increased the vase life of cut hydrangeas by 11.67 days compared to control (from 4.22. to 15.89 days). It also improved solution uptake and delayed relative fresh weight loss. The results showed that 8-HQS is effective in extending the vase life of cut hydrangeas.